Meeting Report from the Second "Minimum Information for Biological and Biomedical Investigations" (MIBBI) workshop. Issue 3 (November 2010) - Kettner, Carsten; Field, Dawn; Sansone, Susanna-Assunta; Taylor, Chris; Aerts, Jan; Binns, Nigel; Blake, Andrew; Britten, Cedrik; Marco, Ario; Fostel, Jennifer; Gaudet, Pascale; González-Beltrán, Alejandra; et al.
Abstract This report summarizes the proceedings of the second workshop of the 'Minimum Information for Biological and Biomedical Investigations' (MIBBI) consortium held on Dec 1–2, 2010 in Rüdesheim, Germany through the sponsorship of the Beilstein-Institute. MIBBI is an umbrella organization uniting communities developing Minimum Information (MI) checklists to standardize the description of data sets, the workflows by which they were generated and the scientific context for the work. This workshop brought together representatives of more than twenty communities to present the status of their MI checklists and plans for future development. Shared challenges and solutions were identified and the role of MIBBI in MI checklist development was discussed. The meeting featured some thirty presentations, wide-ranging discussions and breakout groups. The top outcomes of the two-day workshop as defined by the participants were: 1) the chance to share best practices and to identify areas of synergy; 2) defining a series of tasks for updating the MIBBI Portal; 3) reemphasizing the need to maintain independent MI checklists for various communities while leveraging common terms and workflow elements contained in multiple checklists; and 4) revision of the concept of the MIBBI Foundry to focus on the creation of a core set of MIBBI modules intended for reuse by individual MI checklist projects while maintaining the integrity of each MI project. Further information about MIBBI and its range of activities can be found athttp://mibbi.org/ .